KOMPARATYSTYCZNE STUDIUM HISTORYCZNYCH l WSPÓŁCZESNYCH METOD ORAZ KRYTERIÓW OCENY WIARYGODNOŚCI DOKUMENTÓW - Henryk Streit (In Gremium. Studies in History, Culture and Politics, 2010)
A COMPARATIVE STUDY OF HISTORICAL AND CONTEMPORARY METHODS AS WELL AS CRITERIA USED FOR THE ASSESSMENT OF THE AUTHENTICITY OF DOCUMENTSA significant position of documents in social, political and economic life entails a need to improve methods of verifying documents' authenticity; in t he case of historical documents ir is connected with cognitive purposes o fan academic whereas in the case of contemporary documents it is necessary to provide reliability of documents' circulation.The thesis attempts to prove purposefulness of correlation of methods that are used to assess authenticity of historical and contemporary documents. In order to achieve this a im, I point out possibility and at the same time necessity to take advantage of the examination toolbox used in practice for assessment of authenticity of different forms of contemporary documents in order to check authenticity of historical documents and the other way round.Formal differences, which exist between medieval and early modern diplomas on the one hand and contemporary documents on the other hand, do not constitute a barrier that would preclude using the experience of examining their authenticity.I demonstrate purposefulness of correlation of the above-mentioned methods on the basis of an analysis of diplomatic and paleographic literature concerning methods of examining documents' authenticity and on the basis of chosen documents.Departing from an isolation and Jack of cooperation between diplomatic researchers and representatives of different legal fields, especially criminalistic, will create a platform for versatile kinds of documents' examination.